2017
DOI: 10.1148/radiol.2016160863
|View full text |Cite
|
Sign up to set email alerts
|

Technical Failure of MR Elastography Examinations of the Liver: Experience from a Large Single-Center Study

Abstract: Purpose To assess the determinants of technical failure of magnetic resonance (MR) elastography of the liver in a large single-center study. Materials and Methods This retrospective study was approved by the institutional review board. Seven hundred eighty-one MR elastography examinations performed in 691 consecutive patients (mean age, 58 years; male patients, 434 [62.8%]) in a single center between June 2013 and August 2014 were retrospectively evaluated. MR elastography was performed at 3.0 T (n = 443) or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
105
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 39 publications
8
105
2
3
Order By: Relevance
“…Finally, 31 studies fulfilled the eligibility criteria for our analysis, including eight studies using both GRE and SE‐EPI sequences, 22 studies using only a GRE sequence, , , , , , , , and one study using only an SE‐EPI sequence . As one study using both GRE and SE‐EPI sequences potentially overlapped with a population in another GRE sequence outcome study, we did not include the outcomes of this study in the evaluation of the pooled proportion of technical failure of GRE sequences, but used it only for the head‐to‐head comparison between GRE and SE‐EPI sequences. As a result, we conducted the systematic review and meta‐analyses on 29 studies using GRE sequences and nine studies using SE‐EPI sequences, and compared differences in technical failure rates between the two sequence types using data from eight studies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 31 studies fulfilled the eligibility criteria for our analysis, including eight studies using both GRE and SE‐EPI sequences, 22 studies using only a GRE sequence, , , , , , , , and one study using only an SE‐EPI sequence . As one study using both GRE and SE‐EPI sequences potentially overlapped with a population in another GRE sequence outcome study, we did not include the outcomes of this study in the evaluation of the pooled proportion of technical failure of GRE sequences, but used it only for the head‐to‐head comparison between GRE and SE‐EPI sequences. As a result, we conducted the systematic review and meta‐analyses on 29 studies using GRE sequences and nine studies using SE‐EPI sequences, and compared differences in technical failure rates between the two sequence types using data from eight studies …”
Section: Resultsmentioning
confidence: 99%
“…The demographic characteristics of the included studies are shown in Table . In brief, subjects were enrolled prospectively in 16 studies and retrospectively in 15 studies , , , , , , , . The mean patient ages in 14 studies , , , , , , , , ranged from 25 to 60.5 years, but we could not analyze patient age in the other studies, because they did not report demographic information on all subjects, but reported only those with successful examinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have indicated that steatosis does not have significant effect on MR elastography assessed liver stiffness [97,98,106], although obesity can play a small role in MR elastography failure [107]. Liver stiffness may be elevated in the absence of significant fibrosis in patients with acute alcohol intoxication, acute hepatitis, acute flares of chronic hepatitis, biliary obstruction, chronic inflammation, and passive congestion due to cardiac failure or other cardiac conditions.…”
Section: Magnetic Resonance Elastographymentioning
confidence: 99%
“…The current clinical MR elastography sequence (2D GRE) may fail in patients with moderate to severe hepatic iron deposition [102], contributing to a failure rate in one meta-analysis of 4.3% [93]. Another recent study showed the technical failure rate of MR elastography at 1.5 T was 3.5%, with independent risk factors associated with failure of MR elastography including massive ascites, iron deposition, and high body mass index [107]. This limitation from iron deposition is secondary to the low parenchymal signal, however the shear waves still traverse through the liver but are not visualized and do not have enough signal intensity for post processing by the inversion algorithm.…”
Section: Magnetic Resonance Elastographymentioning
confidence: 99%